2015
DOI: 10.1515/ohs-2015-0033
|View full text |Cite
|
Sign up to set email alerts
|

The increasing aluminum content affects the growth, cellular chlorophyll a and oxidation stress of cyanobacteria Synechococcus sp. WH7803

Abstract: I n t e r n a t i o n a l J o u r n a l o f O c e a n o g r a p h y a n d H y d r o b i o l o g y AbstractEffects of marine aluminum (Al) on phytoplankton are controversial, making it important to elucidate the mechanisms underlying Al effects. This study was aimed at identifying the effects of Al on the growth, chlorophyll a (chl a) content and the antioxidant mechanism of cyanobacteria Synechococcus sp. WH7803. The growth rate increased from 0.33 to 0.52 d -1 in media with the increasing Al concentration fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The enhanced net carbon fixation by the marine diatoms T. weissflogii, T. pseudonana and T. oceanica in the Al-enriched treatments, compared to the controls, is consistent with previous reports of the beneficial effects of Al on the growth of marine phytoplankton (Shi et al 2015;Zhou et al 2016;Liu et al 2018;Zhou et al 2018a). The previous studies showed that Al enhanced the yield of phytoplankton biomass in terms of cell abundance, total cell volume, photosynthetic pigments (i.e., chlorophyll a) and nitrogen fixation.…”
Section: Beneficial Effects Of Al On the Growth And Carbon Fixation Of Marine Phytoplanktonsupporting
confidence: 91%
“…The enhanced net carbon fixation by the marine diatoms T. weissflogii, T. pseudonana and T. oceanica in the Al-enriched treatments, compared to the controls, is consistent with previous reports of the beneficial effects of Al on the growth of marine phytoplankton (Shi et al 2015;Zhou et al 2016;Liu et al 2018;Zhou et al 2018a). The previous studies showed that Al enhanced the yield of phytoplankton biomass in terms of cell abundance, total cell volume, photosynthetic pigments (i.e., chlorophyll a) and nitrogen fixation.…”
Section: Beneficial Effects Of Al On the Growth And Carbon Fixation Of Marine Phytoplanktonsupporting
confidence: 91%
“…Enhanced growth of other marine phytoplankton species (Dunaliella tertiolecta, Tetraselmis sp., and Ceratoneis closterium) in the presence of Al was unexpectedly observed during tests of Al toxicity to marine phytoplankton (Gillmore et al 2016;Golding et al 2015;Saçan et al 2007). Similar stimulatory effects of Al enrichment on marine phytoplankton growth (e.g., Synechococcus sp., Thalassiosira weissflogii and Crocosphaera watsonii) were reported in laboratory studies (Leleyter et al 2016;Liu et al 2018;Shi et al 2015;Shi et al 2016;Zhou et al 2016). Enhanced growth of marine phytoplankton (e.g., Diatoms,…”
Section: Enhanced Growth Of Marine Phytoplankton In the Presence Of Almentioning
confidence: 90%
“…Aluminum toxicity to marine phytoplankton has only been intentionally tested in 1 recent years (Gillmore et al 2016;Golding et al 2015;Harford et al 2011;Saçan et al 2 2007;Xie et al 2015). The influence of Al on the growth, iron (Fe) uptake and 3 physiology of marine phytoplankton has also been reported in other studies (Liu et al 2018;Santana-Casiano et al 1997;Shi et al 2015;Stoffyn 1979;Vrieling et al 1999;5 Zhou et al 2016). Among all the 13 marine phytoplankton species tested (Table S1), the 6 growth of only one diatom Ceratoneis closterium was reported to be inhibited by 7 environmentally relevant Al concentrations (higher than about 10 µg/L or 0.37 µM) in 8 one study (Golding et al 2015), but its growth was reported to be stimulated by low Al 9 concentrations (< 60 µg/L or < 2.2 µM) in another study (Gillmore et al 2016).…”
Section: Al Toxicity To Marine Organismsmentioning
confidence: 99%
“…A varying sensitivity for other marine bacteria is to be expected. In this respect, it is interesting that recent studies have shown that aluminum can even have a stimulative effect on the growth of different cyanobacteria [34,35]. Nevertheless, it can be concluded that bacterial toxicity is unlikely to be the main driver for an environmental risk assessment of galvanic anodes because species from other trophic levels showed higher sensitivities.…”
Section: Discussionmentioning
confidence: 99%